Occurrence of antibody titers against Borna disease virus in alpacas in Bavaria, Germany - Kirmayer, Leonie Isabelle; Lendl, Christine; Wittek, Thomas (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2025)
The increasing population of alpacas in Germany requires comprehensive studies on potential disease. Borna Disease, an infection believed to be primarily transmitted by the bicolored, white-toothed- shrew (Crocidura leucodon) to animals and humans, poses significant concerns. This study aimed to assess the occurrence of Borna Disease virus (BoDV) antibodies in alpacas in Bavaria, Germany, and explore associated epidemiological factors.A total of 424 serum samples were collected from 65 alpaca farms in Bavaria, which were selected voluntarily. In addition, questionnaires were filled out by the animal owners gathering information on husbandry and disease awareness of the owners.The results revealed an occurrence rate of nearly 9%, with one in every fourth farm housing at least one antibody-positive animal. While no significant differences were observed in breed, age, or gender, regional endemic areas were identified, coinciding with the presence of the shrew.This study underscores the widespread occurrence of BoDV antibodies in alpacas in Bavaria, emphasizing the importance of hygiene management and increased awareness of the disease among animal owners and veterinarians.
Keywords: South American camelids; meningoencephalitis; neurological symptoms; zoonosis; seroprevalence